Unsaturated soil mechanics for solving geotechnical problems - Rahardjo, Harianto (2011)
Many geotechnical problems involve unsaturated soils. Some unsaturated soils are also called problematic soils when saturated soil mechanics cannot fully describe the behavior of these soils. Negative pore-water pressure or soil suction in unsaturated soil controls the shear strength and hydraulic properties of the soil such as soil-water characteristic curve and unsaturated permeability function. As a result, water and air flows, volume change and stability problems associated with unsaturated soils are dependent on soil suction. This paper discusses the theories and principles of unsaturated soil mechanics for solving these geotechnical problems with some practical examples to illustrate their applications.